2022
DOI: 10.2196/37683
|View full text |Cite
|
Sign up to set email alerts
|

Digital Devices for Assessing Motor Functions in Mobility-Impaired and Healthy Populations: Systematic Literature Review

Abstract: Background With the advent of smart sensing technology, mobile and wearable devices can provide continuous and objective monitoring and assessment of motor function outcomes. Objective We aimed to describe the existing scientific literature on wearable and mobile technologies that are being used or tested for assessing motor functions in mobility-impaired and healthy adults and to evaluate the degree to which these devices provide clinically valid measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…These technologies cover a big area of the consumer wearable market and lead development trends in sport industry [ 10 , 14 , 15 ]. Wearable devices were the top trend in an electronic survey of health and fitness trends by ACSM’s Health & Fitness Journal for 2022, and they have been estimated to be a $100 billion industry in the US [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These technologies cover a big area of the consumer wearable market and lead development trends in sport industry [ 10 , 14 , 15 ]. Wearable devices were the top trend in an electronic survey of health and fitness trends by ACSM’s Health & Fitness Journal for 2022, and they have been estimated to be a $100 billion industry in the US [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the application of IMUs for upper-limb movement analysis has grown in recent years, though their application is still at an early development stage and is especially targeted to the validation of specific protocols and proof-of-concept systems [26,34,36] and to movement analysis and characterization in specific clinical conditions [31,37]. As far as we are aware, there are only a few studies that have used IMUs to assess performance fatigability directly or indirectly during upper-limb [38,39] tasks, and none, during isometric tasks performed by elderly populations.…”
Section: Introductionmentioning
confidence: 99%
“…Third, reliability characterization for investigational digital measurements is often absent from studies, despite having been acknowledged as an important element for the validation of clinically important research metrics, such as patient-reported outcomes [17]. Beyond step counts, there have been studies that have used other digital measures (eg, walking intensity captured by the peak 30-minute cadence) to generate clinical insights but without full characterization of their performance [18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%